1989
DOI: 10.1111/j.1559-1816.1989.tb01222.x
|View full text |Cite
|
Sign up to set email alerts
|

External Variables, Subjective Expected Utility, and Adolescent Behavior with Alcohol and Cigarettes1

Abstract: A classic social psychological model is that external variables influence behavior through their impact on subjective expected utility, the extent to which more good or harm is expected from behavior. The purpose of this research was to determine whether subjective expected utility is a major intervening variable that links external variables and the onset of alcohol drinking and cigarette smoking. The data are from two longitudinal studies of adolescents. The findings suggest that subjective expected utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…By contrast, according to the limited rationality perspective and consistent with some past research on youth risk taking and on crime (e.g., Bauman et al, 2006;Bauman et al, 1989;Feeney, 1986;Lavery et al, 1993;Parsons et al, 2000;Parsons et al, 1997;Shapiro et al, 1998;Siegel et al, 1994), youths' forecasted engagement in criminal activity would be better predicted simply by a measure of the perceived importance of potential benefits than from a measure that interactively combined the perceived importance of the potential benefits with the subjective probability of the benefits.…”
Section: Competing Views On the Impact Of Risk Perceptions On Criminasupporting
confidence: 80%
See 1 more Smart Citation
“…By contrast, according to the limited rationality perspective and consistent with some past research on youth risk taking and on crime (e.g., Bauman et al, 2006;Bauman et al, 1989;Feeney, 1986;Lavery et al, 1993;Parsons et al, 2000;Parsons et al, 1997;Shapiro et al, 1998;Siegel et al, 1994), youths' forecasted engagement in criminal activity would be better predicted simply by a measure of the perceived importance of potential benefits than from a measure that interactively combined the perceived importance of the potential benefits with the subjective probability of the benefits.…”
Section: Competing Views On the Impact Of Risk Perceptions On Criminasupporting
confidence: 80%
“…For example, Siegel and his colleagues found that engagement in behaviours including alcohol use, illegal drug use, sexual activity, stereotypical male behaviours, imprudent behaviours, and socially unacceptable behaviours by college students as well as adolescents diagnosed with conduct disorder, was better predicted by their perceived benefits of engaging in these behaviours than the perceived costs (Lavery, Siegel, Cousins, & Rubovitts, 1993;Parsons, Halkitis, Bimbi, & Borkowski, 2000;Parsons, Siegel, & Cousins, 1997;Shapiro, Siegel, Scovill, & Hays, 1998;Siegel, Cousins, Rubovitts, Parsons, Lavery, & Crowley, 1994). Bauman and his colleagues measured youths' perceptions of the desirability and probability of the consequences of risky behaviours (e.g., alcohol, tobacco and drug use, and risky sexual behaviour) and found inconsistent evidence for the idea that youths maximize subjective expected utility in past or forecasted risk taking (Bauman & Bryan, 1983;Bauman, Fisher, & Bryan, 2006;Bauman, Fisher, Bryan, & Chenoweth, 1984;1985;Bauman, Fisher, & Koch, 1989;Bauman & Udry, 1981;Gilbert, Bauman, & Udry, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Given its usefulness SEU serves as a foundation in several social psychological models (e.g., Bauman, Fisher, & Koch, 1989;Keeney, See, & von Winterfeldt, 2006), and is applied in a variety of contexts (e.g., Ludemann, 1999;Mehlkop & Graeff, 2010); including ethics research (Farrington & Knight, 1979). Consistent with the SEU framework this study posits that individuals are capable of rating their perceived utilities and indicating their subjective probabilities of realizing those utilities (Holmstrom & Beach, 1973;Kamat & Kanekar, 2001).…”
Section: Buyers' Subjective Expected Utilitymentioning
confidence: 93%
“…We were able to locate only one study that investigated the mediational role of smoking expectancies: In a large sample of adolescents, Bauman et al (1989) found no evidence that expectancies, assessed as UD-SEU, mediate the effects of parental attitudes, closeness with parents, curiosity, and previous experimentation with cigarettes on respondents' current smoking status. Although Bauman et al's null findings fail to support the expectancy-mediation hypothesis, they are by no means conclusive.…”
Section: Smoking Expectancies As Mediatorsmentioning
confidence: 99%
“…One common strategy involves measuring expectancies in terms of unidimensional subjective expected utility (Bauman, Fisher, & Koch, 1989;Fishbein, 1982), hereafter referred to as UD-SEU. Although variations on this approach exist, typically respondents are presented with a list of possible smoking consequences and are asked to rate the probability and desirability of each.…”
Section: Measuring Smoking Expectanciesmentioning
confidence: 99%